2021
DOI: 10.3389/fendo.2021.652807
|View full text |Cite
|
Sign up to set email alerts
|

The Arachidonic Acid Metabolism Mechanism Based on UPLC-MS/MS Metabolomics in Recurrent Spontaneous Abortion Rats

Abstract: Recurrent spontaneous abortion (RSA) remains a critical and challenging problem in reproduction. To discover novel biomarkers for RSA, ultra performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) metabolomics approach was applied to detect RSA serum metabolic profiles and explore its possible pathogenesis and mechanism. The abortion rat model was established, and a metabolomics analysis was performed to evaluate the differentially expressed metabolites between the control and model groups. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Glycerophospholipids induce cyclotoxinase-2 (COX-2), which catalyzes the conversion of arachidonic acid, which plays an important role in female reproduction. Metabolites of arachidonic acid are involved in various reproductive activities such as luteolysis, endometrial gene expression, and development [ 47 ]. Arachidonic acid metabolism plays a crucial role in the inflammatory process [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycerophospholipids induce cyclotoxinase-2 (COX-2), which catalyzes the conversion of arachidonic acid, which plays an important role in female reproduction. Metabolites of arachidonic acid are involved in various reproductive activities such as luteolysis, endometrial gene expression, and development [ 47 ]. Arachidonic acid metabolism plays a crucial role in the inflammatory process [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of arachidonic acid, PGF2α, PGE2 and thromboxane A2 in the amniotic fluid of abortion patients were significantly increased. The release of free arachidonic acid during abortion led to an increase in synthesis of PGF2α, PGE2-prostacyclin and thromboxane A2 in the fetal membranes and decidua, which might be related to abortion process of the patients ( Li et al, 2021 ). Previous studies had shown that PGE2 inhibited the production of Th1 cytokines, but not Th2 cytokines ( Betz and Fox, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse serum was collected, and metabolites were extracted using methanol based on a previously described protocol 44 . Lipid‐related products were separated using UPLC (Sciex ExionLC™ AD) and further analyzed using MS (Sciex QTRAP 6500+) to determine specific m/z values of oxidized lipid products.…”
Section: Methodsmentioning
confidence: 99%